Tourists' motivation and perception (Matang Wilelife Centre) - Lau, Nicholas Pun Ong (Universiti Malaysia Sarawak, 2004)
This survey studies about the Tourists’ Motivation and Perception in Matang Wildlife Centre. The initiative of this research involves factors influencing people visit to the destination and also some studies of human behaviors. 200 respondents were preferred through questionnaires in order to accomplish the analysis from the random samplings. There is no significant relationship between demographic factors and motivation factors at Matang Wildlife Centre. Demographic factors such as age, gender, occupation and nationality have no significant difference with motivation factors.However, race factor has a significant difference with motivation factors. Essentially, every tourist does expect to have the same purpose to visit Matang Wildlife Centre. Financially, most tourists can afford to visit the place, as the entrance fee is affordable.Occupation does not have any significantly effect in tourist motivation as most visitors visit the place on weekends. Working people can spare their time on weekends to visit the place without affecting their working hours. The same goes with the nationality of the visitors. Majority of the visitors are quite satisfied with the cleanliness at Matang Wildlife Centre. This reflects that the cleanliness is an ‘important factor that influences visitor’s attraction.The sufficiency of facilities such as restaurant, BBQ areas, car park, and medical centre would bring convenience to visitors. The staff attitude in Matang Wildlife Centre might not be as important for visitors within age group of 26 to 35 years old because they are capable taking care of themselves. The prices charged at Matang Wildlife Centre arc acceptable for visitor at age of 15 and above.Among the races,’ Chinese is the major group of visitors visiting Matang Wildlife Centre. Majority of the visitors are satisfied with the price set by Matang Wildlife Centre’s management. Only the bumiputera group is dissatisfied with it. Lastly, Matang Wildlife Centre is recommended in ways to improve the facilities as well as other services.